Análisis de la vulneración del principio de igualdad y no discriminación de acciones afirmativas en concursos de méritos y oposición - Cabezas Duchicela, Alisson Lisseth (2024)
ABSTRACT: The main objective of this research study was to focus on merit and competitive examinations to assess cognitive capacity and professional profile under objective parameters aimed at selecting a suitable candidate for public office. Affirmative action claims a benefit concerning the final tentative score of the participants to guarantee material and formal equality together with equal opportunities regarding entry into the public sector. The study was carried out at the Universidad Nacional de Chimborazo to demonstrate a possible violation of the principle of equality and non-discrimination of applicants who do not benefit from such actions. The objective of this project was to analyze through a legal-doctrinal study the application of affirmative actions in merit and competitive examinations and their violation of the principles of equality and non-discrimination. It comprises a nonexperimental research design, of a descriptive legal nature, subject to the legal-analytical, legal-descriptive, and dogmatic methods, where the population was made up of: a) Civil servants subject to the LOSEP regime of the Universidad Nacional de Chimborazo; b) University teachers belonging to the LOES regime within the same institution, to whom the interview guide instrument was applied using the interview technique. As a result, it was determined that the regulation lacking affirmative actions at the normative level generates unjustified practices; there is no equitable score for affirmative actions; it was shown that certain actions are awarded a greater number of points that only give rise to positive discrimination.